International marketing data and statistics 1978/79 (London : Euromonitor Publications, 1978)
One of Euromonitor's best-selling reference books, this has hard-to-find demographic, economic and marketing statistics for 160 non-European countries. Research includes home ownership, health and population statistics. . This publication is widely accepted as one of the most useful sources of statistical documentation and research, it constitutes an invaluable world marketing guide.
Includes index.
rpm 17/08/2018
Loans
Keywords: Statistics; Economic history; Commercial statistics; Market surveys; Marketing international; Marketing; Sociaal-economische situatie; Commerce